2017
DOI: 10.5812/archcid.13914
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and Attitudinal Variables Associated with Acceptance and Willingness to Pay Towards Dengue Vaccine: A Systematic Review

Abstract: Background: Currently, a dengue vaccine has been approved in some countries. The problem with this new vaccine is whether the public could accept and be willing to purchase. Objectives: This study aimed to provide solid data regarding factors associated with acceptance and willingness to pay for dengue vaccine. Methods: A systematic review with a meta-analysis was conducted on September-October 2016 for previous studies. Literatures from PubMed and Embase were searched for eligible publications (cut-off date f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
(37 reference statements)
1
14
1
Order By: Relevance
“…The median WTP rates per parent groups for their self-vaccination were US$86.96 and US$156.52, and for their children’s vaccination were US$108.70 and US$195.65, respectively for Types 1 and 2 DV (Figure 4). The findings from this study suggest very high estimates compared to those reported in previous studies 1517,42,43. The latest study in Vietnam15 estimated the median WTP rate per household at US$26.4 for three doses (around US$32.25 in 2018).…”
Section: Discussioncontrasting
confidence: 50%
“…The median WTP rates per parent groups for their self-vaccination were US$86.96 and US$156.52, and for their children’s vaccination were US$108.70 and US$195.65, respectively for Types 1 and 2 DV (Figure 4). The findings from this study suggest very high estimates compared to those reported in previous studies 1517,42,43. The latest study in Vietnam15 estimated the median WTP rate per household at US$26.4 for three doses (around US$32.25 in 2018).…”
Section: Discussioncontrasting
confidence: 50%
“…In effort to reach this goal, we collected several studies from PubMed and Embase concerning this association to calculate a poolled odd ratio (OR) and 95% confidence interval (CI) using fixed or random effect model. This design of the study was adapted from our previous meta-analysis 51, 52, 53, 54, 55…”
Section: Methodsmentioning
confidence: 99%
“…To reach this goal, several studies regarding the association between hip geometry and femoral neck fractures were collected for calculating combined odds ratios and 95% confidence intervals (ORs 95% CI) and assessed using fixed or random effect model. The design was adapted from our previous studies [20] , [21] , [22] , [23] , [24] . Articles were searched in PubMed and Embase.…”
Section: Methodsmentioning
confidence: 99%